2017
DOI: 10.1016/j.jddst.2017.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and evaluation of antioxidant properties of catechin hydrate nanoparticles

Abstract: A b s t r a c tContext: Catechin hydrate (CH), is an important phyto compound, reported to have potential therapeutic activity for prevention and treatment of various central nervous system (CNS) disorders. However, its therapeutic action is limited by their low oral bio and intestinal absorption, therefore, development of a targeted nanoparticle based carrier system which can overcome its physicochemical limitations and can enhance its biological activity is required. The objective of the pres formulation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In another study, Kaur et al [94] formulated catechin hydrate (CH)-loaded nanoparticles by ionic gelation method by drop wise infusing the anionic polymer (tripolyphosphate) into drug loaded polymeric cationic solution of chitosan, finally leading to the three-dimensional lattice formation. Catechin loaded nanoparticles (CHNPs) showed higher DPPH (67.01 ± 0.15%) scavenging activity as compared to pure CH (65.69 ± 0.34%), similarly better anti-radical and scavenging activity of nitric oxide (NO) (46.12 ± 0.11%) and H 2 O 2 (36.31 ± 0.31%)) as compared to pure CH (NO scavenging = 42.31 ± 0.14% and H 2 O 2 scavenging = 38.12 ± 0.11%).…”
Section: Chitosan Originated Nanocarriermentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Kaur et al [94] formulated catechin hydrate (CH)-loaded nanoparticles by ionic gelation method by drop wise infusing the anionic polymer (tripolyphosphate) into drug loaded polymeric cationic solution of chitosan, finally leading to the three-dimensional lattice formation. Catechin loaded nanoparticles (CHNPs) showed higher DPPH (67.01 ± 0.15%) scavenging activity as compared to pure CH (65.69 ± 0.34%), similarly better anti-radical and scavenging activity of nitric oxide (NO) (46.12 ± 0.11%) and H 2 O 2 (36.31 ± 0.31%)) as compared to pure CH (NO scavenging = 42.31 ± 0.14% and H 2 O 2 scavenging = 38.12 ± 0.11%).…”
Section: Chitosan Originated Nanocarriermentioning
confidence: 99%
“…This improved antioxidant activity dictates the greater efficiency and therapeutic index of encapsulated CH. Moreover, the encapsulation process ensures the slow release of CHNPs (83%, 12 h) with sustainability until 12 h and less cytotoxicity than CH [94]. Chlorogenic acid (CGA), another polyphenolic antioxidant, was encapsulated into chitosan nanoparticles by ionic gelation method, and ensures that the free radical scavenging activity of CGA was restrained and the antioxidant activity of CGA (IC50 value 92 ± 5 µg/mL) is better than unencapsulated CGA (IC50: 89 ± 3 µg/mL) [95].…”
Section: Chitosan Originated Nanocarriermentioning
confidence: 99%
See 1 more Smart Citation
“…Further, graphical representation of the estimated and recorded entrapment efficiency of HCTZ nanocoacervates (Figure 3) showed the correlation between all the optimized parameters and hence, confirms the successful preparation of HCTZ loaded nanocoacervates. 21…”
Section: Resultsmentioning
confidence: 99%
“…We revealed that P. brachycarpa accumulate some phenolic compounds, especially catechin hydrate was highly accumulated in leaves. Many previous reports revealed that catechin hydrate have effect on antioxidant (Mehra et al, 2013;Harper et al, 2010;Kaur et al, 2017;Kassim et al, 2011;Jing et al, 2018;Samanta et al, 2016). In addition to, other report revealed that catechin hydrate has effect on anti-inflammatory (Ashafaq et al, 2012), anti-cancer (Alshatwi, 2010) and improvement of cognitive impairment (Ahmed et al, 2013).…”
Section: Variation In Level Of Phenolic Compounds In the Roots Of P mentioning
confidence: 97%